Exploring issues on the usage of the Bills of Quantities (BQ) and identifying relevant research area - Bandi, Shamsul Hadi; Abdullah, Fadhlin (2012)
Based on past and current studies on BQ, there are concerns on issues relating to the sufficiency and adequacy of the BQ in the current construction environment. Following the preliminary review, detail study has been conducted with an aim to explore the issues further with an attempt to identify and propose relevant research focus in the area. Accordingly, the objectives of this paper are: (1) to critically review the literatures in order to identify the issues on the application of the BQ in the construction industry, and (2) to synthesize the outcome of the review process in order to identify relevant research focus. The study which had essentially employed an extensive literature review had subsequently synthesized and identified eight broad categories of issues concerning the BQ which warrant focus for detail investigation to be carried out. Following this requirement, the study had suggested that research should be focused at appraising the BQ overall adequacy which has been identified to underlie much of the issues as the key area for BQ improvement. Research into the area suggested in this paper would offer substantial improvement to the BQ and is of significant value to the academics and industry alike. The originality of the proposed research is found in addressing the main theme underlying much of the previous studies which, to a certain extent have never been attempted before.